Infrasound as a Cue for Seabird Navigation - Patrick, Samantha C.; Assink, Jelle D.; Basille, Mathieu; Clusella-Trullas, Susana; Clay, Thomas A.; den Ouden, Olivier F. C.; Joo, Rocío; Zeyl, Jeffrey N.; Benhamou, Simon; Christensen-Dalsgaard, Jakob; Evers, Läslo G.; Fayet, Annette L.; et al. (Frontiers in Ecology and Evolution, 2021)
1. Seabirds are amongst the most mobile of all animal species on Earth and spend most of their lives at sea. They cross vast areas of ocean that appear superficially featureless, and our understanding of the mechanisms that they use for navigation remains incomplete, especially in terms of available cues. In particular, several large-scale navigational tasks, such as homing across thousands of kilometers to breeding sites, are not fully explained by visual, olfactory or magnetic stimuli. 2. Low-frequency sound, i.e. infrasound, is ubiquitous in the marine environment. The spatio-temporal consistency of some components of the infrasonic wavefield, and the sensitivity of certain bird species to infrasonic stimuli suggests that infrasound may provide additional cues for navigating seabirds; however, this remains untested. 3. Here, we propose a framework to explore the importance of infrasound for navigation. We present key concepts regarding the physics of infrasound and review the physiological mechanisms through which it may be detected and used. Next, we propose three hypotheses detailing how seabirds could use information provided by different infrasound sources for navigation: as an acoustic beacon, landmark, or gradient. 4. Finally, we reflect on strengths and limitations of our proposed hypotheses, and discuss several directions for future work. In particular we suggest that hypotheses may be best tested by combining conceptual models of navigation with empirical data on seabird movements and in-situ infrasound measurements.